TRANSNATIONAL CORPORATIONS IN KAZAKHSTAN (CENTRAL ASIA AND THE CAUCASUS, 2006)
Obviously, transnational corporations (TNCs) with over 50 percent of world industrial production, over 60 percent of international trade, and nearly 90 percent of foreign direct investments under their control exert considerable influence on the world economy. They have essentially all trade in raw materials under their thumb; Kazakhstan, a country rich in mineral wealth, is also within their range of influence. As an independent state, the republic was not only one of the first in the post-Soviet expanse to attract foreign capital by transferring large enterprises of basic industrial branches to trust management, which allowed subsequent privatization and the setting up of new facilities with 100 percent foreign money, but also relied on intensive mining and extraction as its economic cornerstone. In 1994-1997, the TNCs began their active invasion of Kazakhstan’s economy: after supporting “director” or “bureaucratic” privatization, the government placed its stakes on large foreign investments for obvious reasons. Involvement of large TNCs not only placed the country on the economic map of the world and guaranteed a flow of investments, but also ensured domestic stability (due to interest in protecting property rights). This explains the unprecedentedly wide-scale (as compared to other countries with “transition” economies) involvement of large TNCs in the republic’s economy. The government expected that foreign corporations’ involvement in the local economy through shares and long-term contracts on oil and gas production1 would contribute to the country’s eco- nomic upsurge. It was expected that “the new private owners would not only invest in production, but also introduce new marketing and management skills and, especially, new ideas typical of the market economy.”2 Foreign companies, however, not only and not so much “introduced” “new ideas typical of the market economy” and money, they gained political weight. For obvious reasons, foreign capital created pressure groups. While the country, in the clutches of an economic crisis, badly needed Western money, TNCs, acting as intermediaries between the government and the international financial structures, were primarily lobbying their own interests. Some of them even set up certain public and political movements and organizations. The Civil Party of Kazakhstan, created and supported with the help of the Eurasian Bank,3 is one such structure. The following companies, well known across the world, have struck root in Kazakhstan: Glencore International AG (Kaztsink Open Joint-Stock Company), ENI, Total, Royal Dutch Shell, ExxonMobil, ConocoPhillips, Inpex (Agip KCO Joint-Stock Company), Chevron (Tengizchevroil Ltd.), Samsung (Kazakhmys Corporation), «Mittal Steel» (Mittal Steel Temirtau Joint-Stock Company),4 Philip Morris (Almaty Tobacco Factory Joint-Stock Company), Coca Cola (Coca Cola Almaty Bottlers Joint-Stock Company), and others.5 After settling in Kazakhstan, they promptly mastered the unofficial rules of doing business and fit into the local economic realities. As owners of the largest enterprises, TNCs play an important role in Kazakhstan. Some experts believe that their daughter companies control over 80 percent of the republic’s production potential. For this reason, when dealing with the country’s leaders, they (as distinct from the local business community) are not alien to threats of withdrawing their assets6 from the country’s economy, thus inflicting considerable damage on it. This has happened more than once recently. Orientation toward the interests of foreign corporations is obvious in many spheres: the TNCs are busy lobbying their interests through official and unofficial channels (through key figures in corresponding structures). In particular, the notorious conflict with Tengizchevroil over construction of a gas processing plant was resolved through open lobbying by the Foreign Investors Board.7 The Board was involved in another no less notorious case: at the Board’s plenary sitting held several years ago in the Mangystau Region, A. Mashkevich, President of the Eurasian Industrial Association, complained to President Nazarbaev that the Antimonopoly Committee and the Ministry of Transport had raised transportation tariffs for raw materials, thus infringing on the interests of his transnational industrial-financial conglomerate. The decision was promptly annulled on the basis of only one side’s arguments. It should be said, though, that all sorts of formal channels of cooperation (councils of foreign investors, recommendations on enterprise and investments, etc.) produce a much weaker impact.